Ricardo Palma and the black problematic - Forgues, Roland (2019)
In this essay, the issue of black culture represented in the Peruvian Traditions will be addressed. Being an afro descendant in-between two worlds, the Father of Peruvian literature talked, wrote and behaved as a member of a specific sociocultural group, meanwhile being aware deep inside that his real identity linked him with a different group, what made him feel indebted, either consciously or unconsciously. Besides, this paper will take a closer look to the perspectives from other authors towards the presence of black culture in the Traditions, and we will give a new critical stance.